Construction of functional nanonetwork-structured carbon nitride with Au nanoparticle yolks for highly efficient photocatalytic applications. Issue 52 (11th June 2018) - Leng, Kunyi; Mai, Weicong; Zhang, Xingcai; Liu, Ruliang; Lin, Xidong; Huang, Junlong; Lou, He; Xie, Yiming; Fu, Ruowen; Wu, Dingcai
Abstract : Functional nanonetwork-structured carbon nitride with Au nanoparticle yolks was successfully fabricated, and demonstrated excellent photocatalytic performances. Abstract : We report a novel and versatile fabrication strategy for functional nanonetwork-structured carbon nitride with Au nanoparticle yolks (FNNS-C3 N4 -Au) based on hairy poly(acrylic acid)-grafted SiO2 nanospheres (Au@SiO2 - g -PAA). Benefiting from the three-dimensional nanonetwork structure and well-distributed Au nanoparticles, the as-prepared nanocomposites demonstrated excellent photocatalysis performances (degradation rate constant: 1.8 × 10 −2 min −1 ).